Pre-Assumption of Tess’ Happy Ending as Seen in Tess of The D’ubervilles by Thomas Hardy - Feby Meuthia Yusuf; Ena Zahari (Fakultas Sastra Universitas Ekasakti, 2021)
The object of this research is the struggle of women as reflected by the main character Hardy, namely Tess. The author intends to show how the picture of a woman who never gives up to get a decent life, even though in the end she chose the wrong decision and ended her own life. The approach used in the analysis of women's struggles is a feminist approach, this is intended to provide an ideal view of women in literary works that are the object of male domination. In this research, the writer uses three methods: data collection by applying library research, data analysis using content analysis method that emphasizes the implied and explicit meaning in the fictional character of the literary work, and data representation by compiling the data obtained in systematic writing, namely thesis. The author sees that the character of Tess, as a woman who never gives up in her life. He had made several fatal mistakes which later brought misery and his own end. If only Tess hadn't made that mistake her life would have been for the better. First, if Tess hadn't told her she'd been raped then Angel wouldn't have left her. Second, if Tess didn't reject Angel's intention to return then she would live happily with her husband. Third, if Tess hadn't killed Alec, then she wouldn't have been sentenced to death and could live her life with her husband Angel.